Innovative heating, cooling and ventilation technologies for low-carbon buildings - Mert Cuce, Ayse Pinar (2016)
Sectoral energy consumption analyses clearly indicate that building sector plays a key role in global energy consumption, which is almost 40% in developed countries. Among the building services; conventional heating, ventilation and air conditioning (HVAC) systems have the greatest percentage in total energy consumption of buildings. According to the latest research, HVAC is responsible for around 40% of total building energy consumption and 16% of total global energy consumption. In this respect, decisive measures need to be taken to mitigate the energy consumption due to HVAC. The research carried out within the scope of this thesis covers innovative heating, cooling and ventilation technologies for low-carbon buildings. The novel technologies developed are introduced and investigated both theoretically and experimentally. The results indicate that optimised HVAC systems with waste heat recovery have a significant potential to mitigate energy consumed in buildings, thus to halt carbon emissions. Especially plate-type roof waste heat recovery units are very attractive for the said hybrid applications with a thermal efficiency greater than 88%. The said systems are also promising in terms of overall coefficient of performance (COP). The average COP of plate-type roof waste heat recovery unit is determined to be about 4.5, which is incomparable with those of conventional ventilation systems. Preheating performance of fresh air in winter season is found to be remarkable. Comprehensive in-situ tests clearly reveal that the temperature rise in fresh air is found to be around 7 oC. Plate-type roof waste heat recovery units also provide thermal comfort conditions for occupants. Indoor CO2 concentration is observed to be varying from 350 to 400 ppm which is very appropriate in term of air quality. In addition, average relative humidity is found to be 57%, which is in the desired range according to the latest building standards. Desiccant-based evaporative cooling systems are capable of providing desired indoor environments for occupants as well as having considerably high COP ranges. An average of 5.3 oC reduction is achieved in supply air temperature by utilising those systems as well as having relative humidity distribution in thermal comfort range. The dehumidification effectiveness is found to be 63.7%, which is desirable and promising. The desiccant-based evaporative cooling system has a great potential to mitigate cooling demand of buildings not only in hot arid but also in temperate humid climates.